Large genomic deletions of SMAD4, BMPR1A and PTEN in juvenile polyposis. Issue 5 (4th January 2008) - van Hattem, W A; Brosens, L A A; de Leng, W W J; Morsink, F H; Lens, S; Carvalho, R; Giardiello, F M; Offerhaus, G J A
Abstract : Background/aims: Juvenile polyposis syndrome (JPS) is a rare autosomal dominant disorder characterised by multiple gastrointestinal juvenile polyps and an increased risk of colorectal cancer. This syndrome is caused by germline mutation of either SMAD4 or BMPR1A, and possibly ENG . PTEN, originally linked to Cowden syndrome and Bannayan–Riley–Ruvalcaba syndrome, has also been associated with JPS. By direct sequencing, germline mutations are found in only 30–40% of patients with a JPS phenotype. Therefore, alternative ways of inactivation of the known JPS genes, or additional genes predisposing to JPS may be involved. In this study, a comprehensive genetic analysis of SMAD4, BMPR1A, PTEN and ENG is performed through direct sequencing and multiplex ligation-dependent probe amplification (MLPA) in JPS patients. Methods: Archival material of 29 patients with JPS from 27 families was collected. Direct sequencing and MLPA analysis were performed to search for germline defects in SMAD4, BMPR1A, PTEN and ENG . Results: A germline defect in SMAD4, BMPR1A or PTEN was found in 13 of 27 (48.1%) unrelated JPS patients. Nine mutations (33.3%) were detected by direct sequencing, including six (22.2%) SMAD4 mutations and three (11.1%) BMPR1A mutations. MLPA identified four additional patients (14.8%) with germline hemizygous large genomic deletions, including one deletion of SMAD4, one deletion of exons 10 and 11 of BMPR1A, and two unrelated patients with deletion of both BMPR1A and PTEN . No ENG gene mutations were found. Conclusion: Large genomic deletions of SMAD4, BMPR1A and PTEN are a common cause of JPS. Using direct sequencing and MLPA, a germline defect was detected in 48.1% of JPS patients. MLPA identified 14.8% (4/27) of these mutations. Since a substantial percentage of JPS patients carry a germline deletion and MLPA is a reliable and user-friendly technique, it is concluded that MLPA is a valuable adjunct in JPS diagnosis.